Exploring Macroeconomics, 5e - Sexton, Robert L. (South-Western, 2012)
Exploring Macroeconomics, Fifth Edition, was designed specifically to promote macroeconomic literacy and help students appreciate how macroeconomics affects their everyday lives. This engaging text combines innovative learning tools, a visually appealing design, and captivating content to help students easily absorb information and master key concepts. Packed with examples from current events and pop culture, EXPLORING MACROECONOMICS succeeds like no other book in conveying the excitement and real-world relevance of macroeconomics.